2021
DOI: 10.1021/acssynbio.0c00382
|View full text |Cite
|
Sign up to set email alerts
|

(Optochemical) Control of Synthetic Microbial Coculture Interactions on a Microcolony Level

Abstract: Synthetic microbial cocultures carry enormous potential for applied biotechnology and are increasingly the subject of fundamental research. So far, most cocultures have been designed and characterized based on bulk cultivations without considering the potentially highly heterogeneous and diverse single-cell behavior. However, an in-depth understanding of cocultures including their interacting single cells is indispensable for the development of novel cultivation approaches and control of cocultures. We present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…Indeed in Sinorhizobium meliloti , a nitrogen fixing soil bacterium, the blue-light sensitive transcription factor EL222 was recently used to control production of the public good exopolysaccharide enabling manipulation of biofilm formation 41 . Hybrid optochemical approaches also hold promise for repurposing existing inducible systems, as a recent study showed that photocaged IPTG could be used to control coculture interactions in the bacterium Corynebacterium glutamicum 39 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed in Sinorhizobium meliloti , a nitrogen fixing soil bacterium, the blue-light sensitive transcription factor EL222 was recently used to control production of the public good exopolysaccharide enabling manipulation of biofilm formation 41 . Hybrid optochemical approaches also hold promise for repurposing existing inducible systems, as a recent study showed that photocaged IPTG could be used to control coculture interactions in the bacterium Corynebacterium glutamicum 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Light is a powerful actuator as it is inexpensive, easily controlled in time and space, and S. cerevisiae contains no known native photoreceptors 34 . Light can be rapidly added and removed from cell cultures or spatially targeted 3538 , meaning it can be used to study how regulation of microbial interactions determines microbial community development 3941 . We report here the development of an optogenetic tool that allows the expression of a specific metabolic enzyme of interest to be put under light control in S. cerevisiae .…”
Section: Introductionmentioning
confidence: 99%
“…As a first application, dMSCC was used for lysine production by a consortium consisting of a lysine auxotrophic strain and a strain producing lysine when induced with IPTG. Notably, the use photocaged IPTG with/without deprotection by light demonstrated at the single-cell level that the lysine auxotrophic strain depended on the lysine producing strain ( Burmeister et al, 2021 ). While insight gained by these approaches still needs to be transferred to real-world fermentative processes, we foresee important contributions of microbial consortia to the field.…”
Section: Prospects and Conclusionmentioning
confidence: 99%
“…There is an ever-increasing toolbox of novel genetic parts that can transduce signals into cells: a wide variety of chemically inducible promoters have been developed (Examples in Figure 3A ), 12 of which were demonstrated to be orthogonal when integrated into a single strain of E. coli ( Meyer et al, 2019 ), while new promoters can be mined and developed for other species in the community ( Weinstock et al, 2016 ). Exogenous addition of chemical inducers can be automated: at microscale, computer-controlled syringes can pump chemicals into a microfluidic chamber ( Figure 2 , Input) ( Menolascina et al, 2014 ; Burmeister and Grünberger, 2020 ; Burmeister et al, 2021 ); while at macroscale, cheap bioreactor systems such as Chi.Bio ( Steel et al, 2020 ), the turbidostat designed by Guarino et al (2019) , or the turbidostat of the eVOLVER platform ( Wong et al, 2018 ; Gutiérrez, Kumar and Khammash, 2022 ) removes the need for manual input without expensive or custom-built equipment.…”
Section: Control Input: Actuating Species In a Communitymentioning
confidence: 99%